Long‐term follow‐up of dose‐adjusted EPOCH plus rituximab (DA‐EPOCH‐R) in untreated patients with poor prognosis large B‐cell lymphoma. A phase II study conducted by the Spanish PETHEMA Group. (18th December 2014) - Purroy, Noelia; Bergua, Juan; Gallur, Laura; Prieto, Julio; Lopez, Luis A.; Sancho, Juan M.; García‐Marco, Jose A.; Castellví, Josep; Montes‐Moreno, Santiago; Batlle, Ana; de Villambrosia, Sonia Gonzalez; Carnicero, Fernando; et al.
Summary This prospective multi‐institutional phase II study was designed to assess the efficacy and safety of dose‐adjusted EPOCH (etoposide, prednisone, vincristine, cyclophosphamide and doxorubicin) plus rituximab (DA‐EPOCH‐R) in untreated patients with poor prognosis large B‐cell lymphomas. Eighty‐one patients diagnosed with diffuse large B‐cell lymphoma (DLBCL, n = 68), primary mediastinal DLBCL (n = 6) and follicular lymphoma Grade 3b (n = 7), with an age‐adjusted International Prognostic Index >1, were eligible for analysis. Median age was 60 years (range: 21–77). Sixty‐five patients (80·2%) achieved complete response. After a median follow‐up time of 64 months, 10‐year event‐free survival and overall survival (OS) were 47·8% and 63·6%, respectively. None of the studied clinical and biological characteristics were associated with poorer outcome. Interestingly, patients with BCL6 rearrangement achieved a 10‐year OS of 100%, while patients with BCL2 rearrangement exhibited a poorer outcome compared to activated B‐cell tumours and germinal centre B‐cell without BCL2 rearranged tumours. Results achieved with DA‐EPOCH‐R showed a good long‐term outcome and a tolerable toxicity profile in high‐risk large B cell lymphoma patients. Outcome was not affected by tumour cell proliferation or by cell of origin, highlighting the requirement of new biological markers for patient subclassification of high‐risk DLBCL patients.